Uma jornada pelas trilhas de um processo reflexivo online para coordenadores - Polifemi, Marcos Cesar (2007)
The objective of this study is to describe and interpret the phenomenon of the reflective process of academic coordinators in a continuing education online course, considering for this the perspective of the people who lived this experience: the teacherresearcher and the academic coordinators who were the students of a course entitled education. The theoretical foundations of this piece of research lie in (a) an understanding of teacher education processes which emphasizes the importance of the development of teachers critical and reflective capacity, based on the concepts of Dewey (1916/1994, 1938/1967), Schön (1987, 1991, 1992), Almeida (2005-2006), Freire (1996), Kincheloe (1993/1997), Nóvoa (1995), Perrenoud (2002), Pimenta (2002), Popkewitz (1995), Sacristán (2002), Webb (1996) e Zeichner (1992); (b) a view of learning as socially constituted and prone to be constructed within communities and to become concrete taking as starting points elements that can be found in our routine activities, as discussed by Vygotsky (1934/1984, 1937/1987), Lave & Wenger (1991) and Popper (1972); (c) a concept that sees language from a post-modern perspective, that is, a view that understands meaning as something which is always constructed in relation to some other meaning through a dialogical process that is influenced by the inherent power relationships of our society, as defined by Bakhtin (1929/1995), Foucault (1979) and Graddol (1994); and, (d) a definition of curriculum as a construct that transcends the organization of a syllabus and which is dynamic and open to changes that may adjust the curriculum to better suit the different realities of the learners, according to the ideas of Apple (1990) and Cavallo (2000). The data for this research was collected throughout the development of the course, on a longitudinal basis, for eighteen months, from May 2002 on. My experience with the e-ducation made it possible the investigation of the phenomenon of the reflective process of academic coordinators in a continuing education online course, which was studied thoroughly, during the three modules of the course: the first one dealt with learning strategies, the second one explored the concept of pedagogical common sense, and the third one approached issues related to reflective teaching. Based on the concepts of the Hermeneutic-Phenomenology approach to research, the investigation aimed at describing and interpreting the phenomenon on focus through a thematic interpretation process systematized by Freire (2006), whose work was inspired by a proposal of van Manen (1990). The interpretation of the texts reveals that the phenomenon of the reflective process of academic coordinators in a continuing education online course is structured around four themes: the triggering of reflection, which took place due to a series of strategies used in the course; the mediation of reflection, interpreted through the observation of the teacher s and the students participation throughout the course; the actualization of reflection, related to the moments in which the participants materialize their reflections and share opinions with their colleagues; and the environment for reflection, identified through the observation of specific elements which are essential for the phenomenon studied to take place